2023
DOI: 10.1177/00307270231155257
|View full text |Cite
|
Sign up to set email alerts
|

Commercial uses of antitranspirants in crop production: A review

Abstract: Global food security is at risk due to the predicted climate change, making it imperative for agronomists to provide adaptive technologies that will sustain and improve food production. Rainfed agriculture, prone to drought, covers an estimated 80% of global cropland. One of the adaptive technologies is the use of antitranspirants – products that are applied on plants to reduce transpirational water loss and increase crop performance under drought conditions. The benefits of improving antitranspirant adoption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Antitranspirants are grouped into three classes, based on their mode of action, as metabolic antitranspirants, reflective antitranspirants and film antitranspirants (Mphande et al, 2023). Metabolic antitranspirants, also known as stomata-closing antitranspirants, for example, exogenous abscisic acid (ABA), chitosan and fulvic acid, reduce transpiration by acting on guard cells to induce stomatal closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antitranspirants are grouped into three classes, based on their mode of action, as metabolic antitranspirants, reflective antitranspirants and film antitranspirants (Mphande et al, 2023). Metabolic antitranspirants, also known as stomata-closing antitranspirants, for example, exogenous abscisic acid (ABA), chitosan and fulvic acid, reduce transpiration by acting on guard cells to induce stomatal closure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study done by de Godoi and found sunflower oil to be as effective as di-1-p-methene in reducing transpiration. Antitranspirants are being used commercially in horticulture, but the high cost has limited their use in arable crops (Mphande et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change is increasing the frequency of droughts, which further modifies air CO 2 -O 3 concentrations, reduces precipitation, increases risks of water loss through transpiration, leads to the accumulation of high-temperature records, and promotes more extreme weather events [ 1 , 2 ]. Drought reduces dry mass production and limits physiological activities in medicinal plants, which, together, result in production loss and quality degradation [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, their juvenile stocks are usually cultured in the nursery to shape high-quality stocks for transplant to quickly regenerate a destroyed population at the understory layer. As abiotic stress, drought threatens plant growth and development by impairing botanic functions in the secondary metabolism [ 8 , 9 , 10 ], photosynthetic physiology [ 9 , 10 ], nutrition [ 2 , 8 ], and antioxidation [ 8 ]. Plants can perceive these changes and adjust themselves in multiple ways, resulting in essential adaptations to drought [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One under‐utilised technology is the reduction of plant water loss by using sprays of hydrophobic polymers, such as terpenes, to block stomata, often referred to as film antitranspirants in this role 2 . These products are expensive, and thus currently justified mainly on high value crops or ornamental plants, but, nevertheless, they have potential to increase yield under drought of major global food crops such as wheat and rapeseed 3 . If cheaper polymers could be shown to have similar efficacy to the terpene antitranspirants, then there may be greater likelihood of their adoption for reducing drought damage to food crops, especially by smallholder farmers in low‐income countries.…”
Section: Introductionmentioning
confidence: 99%